Exogenous Galactosylceramide as Potential Treatment for CLN3 Disease. Issue 5 (28th August 2019) - El‐Sitt, Sally; Soueid, Jihane; Maalouf, Katia; Makhoul, Nadine; Al Ali, Jamal; Makoukji, Joelle; Asser, Bilal; Daou, Daniel; Harati, Hayat; Boustany, Rose‐Mary
Abstract : Objective: CLN3 disease is the commonest of the neuronal ceroid lipofuscinoses, a group of pediatric neurodegenerative disorders. Functions of the CLN3 protein include antiapoptotic properties and facilitating anterograde transport of galactosylceramide from Golgi to lipid rafts. This study confirms the beneficial effects of long‐term exogenous galactosylceramide supplementation on longevity, neurobehavioral parameters, neuronal cell counts, astrogliosis, and diminution in brain and serum ceramide levels in Cln3 Δex7/8 knock‐in mice. Additionally, the impact of galactosylceramide on ceramide synthesis enzymes is documented. Methods: A group of 72 mice received galactosylceramide or vehicle for 40 weeks. The effect of galactosylceramide supplementation on Cln3 Δex7/8 mice was determined by performing behavioral tests, measuring ceramide in brains and serum, and assessing impact on longevity, subunit C storage, astrogliosis, and neuronal cell counts. Results: Galactosylceramide resulted in enhanced grip strength of forelimbs in male and female mice, better balance on the accelerating rotarod in females, and improved motor coordination during pole climbing in male mice. Brain and serum ceramide levels as well as apoptosis rates were lower in galactosylceramide‐treated Cln3 Δex7/8 mice. Galactosylceramide also increased neuronal cell counts significantly in male and female mice and tended to decrease subunit C storage in specific brain regions. Astrogliosis dropped in females compared to a slight increase in males after galactosylceramide. Galactosylceramide increased the lifespan of affected mice. Interpretation: Galactosylceramide improved behavioral, neuropathological, and biochemical parameters in Cln3 Δex7/8 mice, paving the way for effective therapy for CLN3 disease and use of serum ceramide as a potential biomarker to track impact of therapies. ANN NEUROL 2019;86:729–742